Biological evaluation of protein nanocapsules containing doxorubicin - Toita, Riki (Dove Medical Press, 2013)
This study describes the applications of a naturally occurring small heat shock protein (Hsp) that forms a cage-like structure to act as a drug carrier. Mutant Hsp cages (HspG41C) were expressed in Escherichia coli by substituting glycine 41 located inside the cage with a cysteine residue to allow conjugation with a fluorophore or a drug. The HspG41C cages were taken up by various cancer cell lines, mainly through clathrin-mediated endocytosis. The cages were detected in acidic organelles (endosomes/lysosomes) for at least 48 hours, but none were detected in the mitochondria or nuclei. To generate HspG41C cages carrying doxorubicin (DOX), an anticancer agent, the HspG41C cages and DOX were conjugated using acid-labile hydrazone linkers. The release of DOX from HspG41C cages was accelerated at pH 5.0, but was negligible at pH 7.2. The cytotoxic effects of HspG41C–DOX against Suit-2 and HepG2 cells were slightly weaker than those of free DOX, but the effects were almost identical in Huh-7 cells. Considering the relatively low release of DOX from HspG41C–DOX, HspG41C–DOX exhibited comparable activity towards HepG2 and Suit-2 cells and slightly stronger cytotoxicity towards Huh-7 cells than free DOX. Hsp cages offer good biocompatibility, are easy to prepare, and are easy to modify; these properties facilitate their use as nanoplatforms in drug delivery systems and in other biomedical applications.